Twentyninth Meeting of the National Development Council January 19 and 20, 1973 Summary Record - Planning Commission (Planning Commission, 1973)
Welcoming the members of the National Development Council, Shrimati Indira Gandhi, Prime Minister stated that at its last meeting the Council had considered the paper outlining the basic ideas which would go into the making of the Fifth Plan. The National Development Council and the Parliament had unanimously endorsed that paper. The two main features of the Plan were removal of poverty and attainment of self-reliance. The next task of the Planning Commission was to work out and suggest a feasible approach to attain these objectives. One basic aim was to achieve higher rates of growth so as to raise the living standards of the people and attain self-reliance. As brought out in the Approach paper, reduction in inequalities and growing self-reliance were complementary and reinforced each other to some extent. The conditions of the poorest sections could be improved only by modifying the pattern of production and increasing the supply of mass consumption goods, particularly food grains and essential commodities. It was also necessary to ensure that these goods were available at reasonable prices. The employment opportunities had to be expanded and a national programme of minimum needs had to be implemented.
Government of India Planning Commission